2009
DOI: 10.1002/qj.432
|View full text |Cite
|
Sign up to set email alerts
|

Differences in raindrop size distribution from southwest monsoon to northeast monsoon at Gadanki

Abstract: Characteristics of raindrop size distribution (DSD) are studied during the southwest (SW) and northeast (NE) monsoon seasons using 4 1/2 years of DSD measurements made at Gadanki (13.5 • N, 79.2 • E) by an impact-type disdrometer. The observed DSD is found to be distinctly different in the NE monsoon from that of the SW monsoon. The stratified DSD (based on rain rate) shows more small drops and fewer bigger drops in the NE monsoon than in the SW monsoon, particularly in the low rain rate regime. This feature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 23 publications
(38 reference statements)
3
24
1
Order By: Relevance
“…This characteristic of DSD shows the wet spells has higher rainwater content and rainfall rate, which will be discussed in the later sections. These results are distinctly different from the previous studies over other regions, e.g., Konwar et al (2006), Rao et al (2009), and Harikumar et al (2016). Harikumar et al (2016) observed a higher number of larger drops at three different stations located in southern India.…”
Section: Average Raindrop Spectracontrasting
confidence: 99%
See 2 more Smart Citations
“…This characteristic of DSD shows the wet spells has higher rainwater content and rainfall rate, which will be discussed in the later sections. These results are distinctly different from the previous studies over other regions, e.g., Konwar et al (2006), Rao et al (2009), and Harikumar et al (2016). Harikumar et al (2016) observed a higher number of larger drops at three different stations located in southern India.…”
Section: Average Raindrop Spectracontrasting
confidence: 99%
“…Harikumar et al (2016) observed a higher number of larger drops at three different stations located in southern India. Konwar et al (2006) and Rao et al (2009) showed that stratiform precipitation dominates over Gadanki. However, shallow convection occurs frequently over WGs (Utsav et al, 2017).…”
Section: Average Raindrop Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…, is obtained from the rainy samples of Taiwan (7,466 samples) and Palau (18,868 samples) and are shown with blue and red colors, respectively, in Figure 3a. In the present study, raindrop diameter classification (small, middle, and large size drops) proposed by previous researchers (Jayalakshmi & Reddy, 2014;Krishna et al, 2016;Narayana Rao et al, 2009;Tokay et al, 2008) is adapted to explain the RSD variations. Raindrops of diameter less than 1 mm are considered as small drops, 1 to 3 mm as middle-size drops, and above 3 mm as large drops.…”
Section: Observational Resultsmentioning
confidence: 99%
“…It is observed that the total data set, and constrained data set are in the same proportion in the distribution. This indicates the homogenous distribution of raindrops and wind velocity in all rain rates, which is the unique feature of monsoon (Narayana Rao et al, ). In the postmonsoon season, the rain rates are dispersed and concentrated on high and low rain rate extreme values.…”
Section: Resultsmentioning
confidence: 99%